Predictive modelling for late rectal and urinary toxicities after prostate radiotherapy using planned and delivered dose - Ong, Ashley Li Kuan; Knight, Kellie; Panettieri, Vanessa; Dimmock, Mathew; Tuan, Jeffrey Kit Loong; Tan, Hong Qi; Wright, Caroline (Frontiers in Oncology, 2022)
Background and purpose: Normal tissue complication probability (NTCP) parameters derived from traditional 3D plans may not be ideal in defining toxicity outcomes for modern radiotherapy techniques. This study aimed to derive parameters of the Lyman-Kutcher-Burman (LKB) NTCP model using prospectively scored clinical data for late gastrointestinal (GI) and genitourinary (GU) toxicities for high-risk prostate cancer patients treated using volumetric-modulated-arc-therapy (VMAT). Dose-volume-histograms (DVH) extracted from planned (DP) and accumulated dose (DA) were used. Material and methods: DP and DA obtained from the DVH of 150 prostate cancer patients with pelvic-lymph-nodes irradiation were used to generate LKB-NTCP parameters using maximum likelihood estimations. Defined GI and GU toxicities were recorded up to 3-years post RT follow-up. Model performance was measured using Hosmer-Lemeshow goodness of fit test and the mean area under the receiver operating characteristics curve (AUC). Bootstrapping method was used for internal validation. Results: For mild-severe (Grade ≥1) GI toxicity, the model generated similar parameters based on DA and DP DVH data (DA-D50:71.6 Gy vs DP-D50:73.4; DA-m:0.17 vs DP-m:0.19 and DA/P-n 0.04). The 95% CI for DA-D50 was narrower and achieved an AUC of >0.6. For moderate-severe (Grade ≥2) GI toxicity, DA-D50 parameter was higher and had a narrower 95% CI (DA-D50:77.9 Gy, 95% CI:76.4-79.6 Gy vs DP-D50:74.6, 95% CI:69.1-85.4 Gy) with good model performance (AUC>0.7). For Grade ≥1 late GU toxicity, D50 and n parameters for DA and DP were similar (DA-D50: 58.8 Gy vs DP-D50: 59.5 Gy; DA-n: 0.21 vs DP-n: 0.19) with a low AUC of <0.6. For Grade ≥2 late GU toxicity, similar NTCP parameters were attained from DA and DP DVH data (DA-D50:81.7 Gy vs DP-D50:81.9 Gy; DA-n:0.12 vs DP-n:0.14) with an acceptable AUCs of >0.6. Conclusions: The achieved NTCP parameters using modern RT techniques and accounting for organ motion differs from QUANTEC reported parameters. DA-D50 of 77.9 Gy for GI and DA/DP-D50 of 81.7-81.9 Gy for GU demonstrated good predictability in determining the risk of Grade ≥2 toxicities especially for GI derived D50 and are recommended to incorporate as part of the DV planning constraints to guide dose escalation strategies while minimising the risk of toxicity.